Igh-6(-/-) (B-cell-deficient) mice fail to mount solid acquired resistance to oral challenge with virulent Salmonella enterica serovar typhimurium and show impaired Th1 T-cell responses to Salmonella antigens. - Mastroeni, P; Simmons, C; Fowler, R; Hormaeche, C; Dougan, G (2000)
In the present study we evaluated the role of B cells in acquired immunity to Salmonella infection by using gene-targeted B-cell-deficient innately susceptible mice on a C57BL/6 background (Igh-6(-/-)). Igh-6(-/-) mice immunized with a live, attenuated aroA Salmonella enterica serovar Typhimurium vaccine strain showed impaired long-term acquired resistance against the virulent serovar Typhimurium strain C5. Igh-6(-/-) mice were able to control a primary infection and to clear the inoculum from the reticuloendothelial system. However, Igh-6(-/-) mice, unlike Igh-6(+/+) C57BL/6 controls, did not survive an oral challenge with strain C5 at 4 months after vaccination. Transfer of immune serum did not restore resistance in Igh-6(-/-) mice. Total splenocytes and purified CD4(+) T cells obtained from Igh-6(-/-) mice 4 months after vaccination showed reduced ability to release Th1-type cytokines (interleukin 2 and gamma interferon) upon in vitro restimulation with serovar Typhimurium soluble cell extracts compared to cells obtained from Igh-6(+/+) C57BL/6 control mice. Therefore, the impaired resistance to oral challenge with virulent serovar Typhimurium observed in B-cell-deficient mice, which cannot be restored by passive transfer of Salmonella-immune serum, may be in part due to a reduced serovar Typhimurium-specific T-cell response following primary immunization.